Determinan Kualitas Audit: Peran Kompetensi Auditor, Teknik Audit Berbantuan Komputer, dan Tekanan Anggaran Waktu - R. Bisma Aliansyah Putra; Nurul Mustafida (Politeknik Raflesia Press, 2025)
This study analyzes the influence of auditor competence, computer-assisted audit techniques (CAATs) and time budget pressure on audit quality at Public Accounting Firms in Surabaya. It aims to identify the factors affecting audit quality using a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method. Primary data were collected through offline-distributed questionnaires targeting auditors working at Public Accounting Firms in Surabaya resulting in 72 valid responses out of 119 collected. The findings indicate that auditor competence does not significantly affect audit quality likely due to variations in education levels and work experience among auditors. In contrast the use of CAATs positively impacts audit quality by enhancing the efficiency and accuracy of audit analysis. Meanwhile time budget pressure does not exhibit a significant effect on audit quality possibly due to the auditor's position